SOCIAL REPRESENTATIONS AND BEHAVIORAL ASPECTS OF FEMALE ORGASM - Uhlmann, Walmiria Walter (2024)
This study investigated elements of women's social representations and behavioral aspects of orgasm. 180 women from three different age groups took part: 18-29 years, 30-59 years and 60 years and over. The data collection instrument was an online questionnaire made up of 37 items. The data was analyzed using descriptive statistics and lexicographic analysis techniques. The results show that representations of orgasm vary according to age: younger women emphasize physical pleasure and masturbation, while older women associate orgasm with intimacy and emotional satisfaction. In addition, a change in sexual practices was observed over time, possibly related to changes in social representations of female sexuality. This study reveals the transformations in the understanding and experience of female sexuality over the generations, influenced by socio-cultural changes and the growing search for autonomy and sexual freedom.